Examining the Factor Structure of the Voice Disability Coping Questionnaire in Individuals With Laryngeal Dystonia and Essential Vocal Tremor. - Welch, Brett; Lewandowski, Ali; Gartner-Schmidt, Jackie; Smith, Libby J. (Journal of Speech, Language & Hearing Research, 2025)
Purpose: The purpose of this study is twofold. First, we sought to replicate the reported factor structure of the Voice Disability Coping Questionnaire (VDCQ) in a sample of patients diagnosed with a chronic voice disorder. Second, we sought to examine how the factors of the VDCQ relate to perceived voice handicap and perceived stress in these patients. Method: Participants diagnosed with laryngeal dystonia (n = 78) and/or essential vocal tremor (n = 27) were recruited to participate in a cross-sectional survey research study. Participants completed the VDCQ, the Voice Handicap Index-10 (VHI-10), the Perceived Stress Scale-4 (PSS-4), and self-reported overall coping. Part 1 uses common factor analysis to test the hypothesized factor structure of the VDCQ. Part 2 uses structural equation modeling (SEM) to examine the hypothesized relationships between the VDCQ factors and the other measures. Results: Confirmatory factor analysis did not support the VDCQ's hypothesized three- or four-factor solutions. Subsequent exploratory factor analysis demonstrated a two-factor solution fit the data well, that is, Proactive Social Coping and Passive/Avoidant Coping. Results of the SEM demonstrate that the Passive/ Avoidant Coping factor is significantly associated with the VHI-10 and PSS-4 and inversely related to self-reported overall coping. Conclusions: Although neither the original three- or four-factor solution fit the data well, this study provides additional psychometric support for a two-factor solution of the VDCQ. These two factors closely resemble the initial factor structure and meaningfully relate to perceived vocal handicap, stress, and perceived overall coping. Supplemental Material: https://doi.org/10.23641/asha.30369775